Efficacy of 3% hypertonic saline nebulization in children hospitalized with moderate bronchiolitis - Radhakrishnan, Rajkumar C.; Padmanabhan, Ramkumar A. (International Journal of Contemporary Pediatrics, 2018)
Background: Bronchiolitis is one of the most common lower respiratory tract viral infections within the first 2 years of life; more than one third of children develop bronchiolitis. Of these, 1 out of 10 children will be hospitalized. Methods: We did interventional, randomized control study of 3% hypertonic saline nebulization to 100 moderate bronchiolitis children admitted during our study period of 18 months. Primary outcome of duration of hospital stay and secondary outcome of Cough resolution time, wheeze resolution time are analyzed. No side effects or adverse drug reactions are observed. Results: There was a 3.9 percentage reduction in length of stay in the hypertonic saline group compared to the control group which received supportive therapy alone. But these findings were not statistically significant. The cough resolution time and the wheeze resolution time were statistically significant shorter duration in the study group than the control group. Conclusions: Nebulized hypertonic saline significantly reduced the cough and wheeze resolution time but not significantly reduced the hospital stay.